Personalized Physical Therapy Versus Usual Care for Patients With Systemic Sclerosis: A Randomized Controlled Trial. Issue 7 (7th June 2017) - Rannou, François; Boutron, Isabelle; Mouthon, Luc; Sanchez, Katherine; Tiffreau, Vincent; Hachulla, Eric; Thoumie, Philipe; Cabane, Jean; Chatelus, Emmanuel; Sibilia, Jean; Roren, Alexandra; Berezne, Alice; et al.
Abstract : Objective: To compare a physical therapy program to usual care of systemic sclerosis (SSc) patients on disability. Methods: A 12‐month followup, parallel‐group randomized controlled trial involving a modified Zelen design was conducted in 4 tertiary‐care hospitals. Patients were enrolled if they had a disability rating ≥0.5 on the Health Assessment Questionnaire disability index (HAQ DI) or symptoms of decreased mouth opening or limited range of motion of at least 1 joint. The experimental intervention (n = 112, of which 110 were analyzed) was a 1‐month personalized supervised physical therapy program provided by trained care providers followed by home sessions. The comparator (n = 108, and all 108 were analyzed) was usual care that could include ambulatory physical therapy. The primary outcome was the HAQ DI score. Results: There was no statistically significant difference in disability at 12 months (HAQ DI score between‐group difference −0.01 [95% confidence interval (95% CI) −0.15, 0.13]; P  = 0.86). Disability was reduced at 1 month for patients in the physical therapy group (HAQ DI between‐group difference −0.14 [95% CI −0.24, −0.03]; P  = 0.01); at 6 months the HAQ DI score between‐group difference was −0.12 (95% CI −0.23, 0.01); P  = 0.054. There was a statistically significant difference for hand mobility and function, and for pain, at 1 month. Microstomia was lower in the physical therapy group at 1, 6, and 12 months (between‐group difference at 12 months 1.62 [95% CI 0.32, 2.93]; P  = 0.01). No differences in adverse effects were observed. Conclusion: A personalized physical therapy program did not reduce disability at 12 months but had short‐term benefits for patients with SSc.